Economic efficiency of network-based solar power stations employment in private housing estates - Клён, Андрей Николаевич; Ефременко, Виктория Викторовна (Technology audit and production reserves, 2015)
This paper focuses on the economic efficiency issues and the peculiarities of private network-based solar power stations establishing in Ukraine. There have been determined the possibilities of “green” tariff usage. There have been calculated capitalized and current charges incurred by housing estates in case of network-based solar power stations employment, profit due to the electricity output at the solar power station, payback period upon their employment. As a result of the research conducted by the authors, they have reached a conclusion that network-based solar power stations return a profit only at sufficiently high capacity and providing their connection to the ‘green’ tariff. The maximum profits at the minimum payback period are returned by the power stations with the capacity close to the maximum, acceptable for the ones in private housing estates. It is worth mentioning that the main deterrent restraining the mass employment of solar power stations in Ukrainian private housing estates are sufficiently large initial expenses. Besides, an important factor in successful realization of projects on establishing network-based solar power stations in private housing estates is the support on behalf of the state.